Strategi Pemasaran dalam Upaya Peningkatan Omset Penjualan UMKM Desa Sumber Kembar, Kecamatan Pacet, Kabupaten Mojokerto - Nikmatus Sholicha; Renny Oktafia (Jurnal Ilmiah Ekonomi Islam, 2021)
Micro, Small and Medium Enterprises (MSME) in Indonesia have an increasing number from year to year. Starting from 2012 to 2017 the development of MSME reached 13.98 percent. percentage in 2017, MSME have reached the number of 62,922,617 units in various regions in Indonesia, of course the number is much larger than the large businesses that only amounted to 5,460 units. Largest amount was donated by micro businesses as much as 62 million (98.7 percent), with small and medium enterprises amounting to 815 thousand units or only 1.3 percent. Sumber Kembar village is also a contributor to the unit. but still have difficulty in implementing the right marketing strategy. Research aims to know the implementation of marketing strategies in an effort to increase the sales turnover of MSME Sumber Kembar village and as an education on the impact caused. type of research method used qualitatively with case study approach. MSME in the village use offline steps in a product marketing that makes their turnover small and the business difficult to develop. if the MSME in Sumber Kembar village do not follow the development of technology, then they will be difficult to compete with other competitors who have advanced.